Ruminative thought style and workplace ostracism’s effects on hotel employees’ turnover intention: the mediating effect of organisational identification - Turkoglu, Nuray (2019)
This study’s primary objective was to examine ruminative thought style and workplace ostracism’s effects on hotel employees’ turnover intention. A secondary objective was to investigate these effects through the mediator role of organisational identification. The data were collected by convenience sampling between 1 June and 1 October 2018 from employees of 12 5-star hotel businesses in Bodrum, Turkey, yielding 432 valid survey forms. The results show that ruminative thought style and workplace ostracism increase hotel employees’ turnover intention, while organisational identification decreases it. In addition, the latter variable plays a significant mediating role between ruminative thought styles and turnover intentions. Thus, managers need to create good working environments, support and participate in social activities with their team, make employees feel that they are a part of their organisation and frequently reiterate that each team member is valued.